College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 8 - Sequences, Induction, and Probability - Exercise Set 8.1 - Page 717: 100



Work Step by Step

False, e.g. $\sum_{i=1}^{2} (-1)^i2^i=((-1)^12^1)+((-1)^22^2)=-2+4=2$ but $\sum_{i=1}^{2} (-1)^i\sum_{i=1}^{2}2^i=((-1)^1+(-1)^2)(2^1+2^2)=(-1+1)(2+4)=0\cdot6=0$ and $2\ne0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.